EDUKASI NILAI-NILAI ISLAM DALAM MENCEGAH PERMASALAHAN SOSIAL DI DESA KARANGREJA KECAMATAN PEBAYURAN - Irfanudin, Hafidz; Shabah, Musyaffa Amin Ash; Supriyanto, Agus (Al-Ihsan: Journal of Community Development in Islamic Studies, 2024)
The increasingly widespread moral crisis, especially among teenagers, requires a strategic solution to save the character of the nation's next generation. One effective effort is through Islamic values education and the active role of parents in shaping noble morals. This service aims to educate the people of Karangreja Village about the importance of studying as a Muslim obligation in order to create individuals who are morally upright and able to make a positive contribution to the surrounding environment. The service method used is an educational approach through counseling activities, group discussions, and training based on Islamic values. This program involves various elements of society, especially teenagers, to understand the essence of knowledge in distinguishing between good and bad, and encourages them to share useful knowledge as recommended by Islam. The results of the service showed an increase in community awareness about the importance of knowledge in building a strong character and preventing social problems. Youth in Karangreja Village began to actively participate in faith-based activities, and showed more positive and productive behavioral changes. This program not only strengthens Islamic values, but also instills collective awareness of social responsibility in maintaining the morals of the younger generation. This effort is expected to contribute to creating a harmonious and religious community environment.